Can the Recall Improve Electoral Representation? - Vandamme, Pierre-Etienne (Frontiers in Political Science, 2020)
Empirical studies reveal many citizens' unwillingness to get rid of representative democracy. A great number of them, however, distrust their representatives and would want representation to be improved, for example by giving citizens more control over their representatives. One possible mechanism of control is the recall—the possibility to remove elected representatives from office through a vote before the end of their term. Although this democratic tool is on the rise worldwide and was supported in the past by influential figures such as Rousseau and Marx, its study has been neglected by contemporary political theorists. The aim of this contribution is to identify the main arguments for and against the use of recall mechanisms, and to assess both their normative and empirical validity. In particular, it asks whether they have the capacity to improve the quality of representation or at least the perception of representative institutions' legitimacy, and answers with a moderate “yes”—especially for the latter aspect (perceived legitimacy).